Analisis Dampak Pemberdayaan Sadar Wisata Pelabuhan Dengan Konsep Ekonomi Biru Berorientasi Potensi Lokal Bagi Masyarakat Kota Probolinggo - Lailatul Fitria, Nurul Jannah; Supriyanto (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
The central government and local governments require commitment and coordination of marine tourism development relevant to the regulation of Law Number 10 of 2009 concerning Tourism. Probolinggo City as an area with authority ownership of marine areas. In Probolinggo City, there is Tanjung Copper Port with quality and superior marine and fisheries potential. So that it requires cohesiveness and participation according to the roles and duties of each actor. One of the strategies carried out by the government is the uniformity of goals, the dissemination of policies, the improvement of knowledge related to the management of tourist areas and the utilization of marine resources, and others through empowerment. Such an empowerment activity is the conscious empowerment of port tourism with the concept of blue economy oriented to local potential in Probolinggo City. This is interesting to study to find out the impact of this empowerment for partners or communities in tourism awareness with local potential according to the principles of the blue economy. This research uses descriptive qualitative methods with a case study approach in Probolinggo City. The focus of the research is a conceptual study related to indicators of empowerment success. The results showed that partners understood the importance of local tourism awareness, especially local tourism in the Probolinggo City Port Complex. As well as added understanding of tourism development in the Probolinggo City Port Complex must be developed with the concept of blue economy and orientation to the utilization of local potential. Measurement of partner acceptance and understanding of the material presented in more detail in four indicators of conceptual studies related to empowerment, including partners showing increased awareness and desire to change, increased ability in role capacity to gain access to participation, increased ability to deal with existing obstacles within the scope of the Probolinggo City port, and increased ability for cooperation and solidarity.